Association between poor parent-daughter relationships and the risk of hyperglycemia in pregnancy: a hospital-based prospective cohort study in Japan - Yuto Maeda; Satomi Doi; Aya Isumi; Shuhei Terada; Junichi Sugawara; Kazuhisa Maeda; Shoji Satoh; Nobuaki Mitsuda; Takeo Fujiwara (BMC, 2023)
Abstract Background Adverse child experiences (ACEs), childhood maltreatment and household dysfunction, are risk factors of hyperglycemia in pregnancy (HIP), including diabetes before pregnancy, gestational diabetes (GDM), and overt diabetes in pregnancy, through increased risk of unhealthy behaviors, obesity, and stress response system dysfunction. While ACEs are often difficult to be assessed in hospital settings, parent-daughter relationship, that is, pregnant women's relationship with their parents can be considered as a measurable maker for ACEs that may be associated with HIP. The purpose of this study is to examine the association between poor parent-daughter relationship and HIP. Methods Hospital-based prospective cohort study was conducted in Japan (N = 6,264). Women visiting participating 58 facilities for delivery between April 2019 and March 2020 were included. Parent-daughter relationship was assessed by a questionnaire asking whether participants were satisfied with their relationship with their parents. HIP was diagnosed based on the criteria used in Japan. A multiple logistic regression model was applied to adjust for covariates. Results Pregnant women who were not very satisfied and not satisfied at all with the relationship with their parents, and HIP were 343 (5.5%), 74 (1.2%), and 274 (4.4%), respectively. Pregnant women who were not very satisfied with their parent-daughter relationship showed a significant positive association with HIP in the crude model (odds ratio (OR): 1.71, 95% confidence interval (CI): 1.11-2.63). When stratified by psychiatric disease history, we found a significant positive association among those without psychiatric disease history (OR: 1.77, 95% CI: 1.11-2.84), but not among those with psychiatric disease history (OR: 0.61, 95% CI: 0.16-2.28). Conclusions Poor parent-daughter relationship was associated with the risk of HIP among pregnant women without psychiatric disease history, suggesting that this simple question could be used to estimate the risk of HIP when it was challenging to inquire directly about ACEs. Further research is needed to elucidate the mechanism of the association.